Penatalaksanaan Holistik Osteoarthritis Dan Obesitas Derajat 2 Pada Wanita Usia 69 Tahun Melalui Pendekatan Dokter Keluarga - Abiyyi Pratama HW; Firinfa Soniya; Fitria Saftarina (Medula, 2022)
Osteoarthritis (OA) is a degenerative disease of the joints caused by several factors there are age, gender, race, genetics, trauma, occupation (activity), and obesity. Based on data from the WHO 2019, the prevalence of joint disease is reported to be 40% of the world's elderly population will suffer from OA, which 80% have limited joint motion. The causes of pain that occur are multifactorial. Obesity is the strongest modifiable risk factor in OA patients. During activity, half of the body weight rests on the joints. An increase in body weight will double the load on the joints when walking, especially the knee joints. Patient Mrs. N, 69 years old, came to the Panjang health center on November 11, 2021 with complaints of pain and stiffness in the joints in the right and left knees since 1 week ago. The complaints were felt continuously, especially when the patient often walked. Pain is felt in the right and left knees. The duration of complaints of pain appears less than 30 minutes.The pain is felt like a stabbing and comes and goes, especially in the morning after waking up. On physical examination, the body weight was 87 kg, height 168 cm, BMI 33.98. The diagnosis in this patient was Osteoarthritis (OA) and 2nd Grade Obesity.Management is carried out holistically for patients and families through flipchart intervention media in the form of information about OA and obesity and also suggests recommended activities for patients. Holistic management based on Evidence Based Medicine through patient-centered and family approaches can improve knowledge, attitudes and behavior on the patient